Computational Investigation of the 1, 4‐Rh Shift in the [(Ph2PCH2CH2PPh2)Rh]‐Catalyzed Alkyne Arylation Reaction. Issue 32 (6th October 2015) - Kantchev, Eric Assen B.; Zhou, Feng; Pangestu, Surya R.; Sullivan, Michael B.; Su, Haibin
Abstract: Computations (density functional theory) of the post‐transmetallation stages (carborhodation, 1, 4‐shift consisting of C–H oxidative addition/C–H reductive elimination, and hydrolysis) in the catalytic cycle for the arylation of 2‐butyne with phenylboronic acid mediated by [(dppe)Rh I ] catalyst [dppe = 1, 2‐bis(diphenylphosphanyl)ethane] shows that (1) carborhodation is facile (Δ G ‡ ≈ 10 kcal mol –1 ); (2) the barriers of the 1, 4‐shift and hydrolysis are approximately equal (Δ G ‡ ≈ 19–24 kcal mol –1 ); (3) the 1, 4‐Rh shift product is ca. 5 kcal mol –1 more stable than the non‐rearranged product, in good agreement with the experimental results. Analogous computations for ( Z )‐2‐butene as a model substrate show that (1) carborhodation is much slower (Δ G ‡ ≈ 19 kcal mol –1 ); (2) the sp 3 → sp 2 1, 4‐shift is faster than the sp 2 → sp 2 1, 4‐shift; (3) the hydrolysis of Rh–C σ bonds depends more on the steric environment than the hybridization of the C atom; and (4) β‐hydride elimination is the most likely reaction after carborhodation. Abstract : DFT computations for the arylation of 2‐butyne with phenylboronic acid mediated by [(dppe)Rh I ] [dppe = 1, 2‐bis(diphenylphosphanyl)ethane] reveal that (1) carborhodation is fast; (2) the barriers of the 1, 4‐shift and hydrolysis are approximately equal; and (3) the 1, 4‐Rh shift product is ca. 5 kcal mol –1 more stable than the non‐rearranged product, in good agreement with the experimental results.